“Blood for blood”: David Fanning and retaliatory violence between Tories and Whigs in the revolutionary Carolinas - Mayr, Gregory (My University, 2014)
This paper, relying primarily on Loyalist Colonel David Fanning’s personal narrative of the American Revolution, will argue that Fanning applied, in some of his actions, a form of retributive reasoning similar to that described by Historians Wayne E. Lee and Jeffrey J. Crow as typical for the revolutionary Carolinas. In Fanning’s case, the code by which he decided what to do in given situations was more complex than a one-dimensional law of retaliation; Fanning made an effort to incorporate conventional forms of honor into his actions, but harbored a great deal of distrust for his adversaries that came out of the experiences he had during the Revolution with his Whig opponents. His targets were purposive, aimed at Whig leadership, supplies and government officials. Fanning’s level of violence escalated toward the end of the revolution due to his genuine disdain for the rebels and his resentment at fighting what he eventually acknowledged to be a losing war.
Keywords: David Fanning; Retaliation; Retribution; lex talionis; Thomas Burke